An Early Hearing Detection and Intervention Program in Songklanagarind Hospital - Khaimook, Wandee; Suwanno, Roj; Dindamrongkul, Ramida; Intusoma, Utcharee (Journal of Health Science and Medical Research, 2023)
Objective: To compare the results of the universal newborn hearing screening program in Songklanagarind Hospital with the Joint Committee of Infant Hearing (JCIH) recommendations in regards to early hearing detection and intervention. Material and Methods: We retrospectively reviewed the Early Hearing Detection and Intervention (EHDI) program results between January 2017 and June 2017. Furthermore, we calculated and compared the percentages of hearing screening, diagnostic evaluation, and rehabilitation at 1, 3, and 6 months of age. Results: A total of 1,579 (93.1%) newborns were screened for otoacoustic emissions (OAEs). One hundred and eight (6.8%) newborns showed abnormal OAE in the first phase, and 11 (0.7%) newborns failed the OAE retest before discharge and within 1 month of age. Ten newborns (90.9%) had a hearing loss diagnosis confirmed due to a complete audiologic evaluation before 3 months of age, and 100.0% of newborns with abnormal hearing were enrolled for intervention within 6 months of age. Among the 4 newborns with abnormal hearing, 3 of them had conductive hearing loss, and one had profound sensorineural hearing loss, receiving an intervention via cochlear implant. Following intervention, all newborns with hearing loss had improved their hearing ability, speech and language development. Conclusion: The universal newborn hearing-screening program is the first step in identifying a child with hearing problems, which leads into early intervention. The key to achieve best outcomes for the newborns is to ensure family support and the involvement of an interdisciplinary team.